Preface of JAS-01-01-2024 - The Editors-in-Chief of JAS (Journal of Approximation Software, 2024)
We have the pleasure to present the first issue of the Journal of Approximation Software. It publishes in open-access mode well-structured accompanying articles to open-source software, on all aspects of approximation theory and applications in its broadest sense. The publisher is University of Torino (Italy) by its open-access platform SIRIO@UniTO. Implementations can use the most common languages and environments like MATLAB, Python, C, C++, among others. The codes are posted by the authors on stable public platforms with a clear software versioning policy, such as GitHub. There will be one general issue per year (with articles published continuously by acceptance date) and possible thematic special issues including conference proceedings. This first issue collects a few regular articles of colleagues and researchers, who work in different fields of approximation implementing numerical algorithms by means of the MATLAB software. The issue includes a variety of approximation topics involving exponential integrators, ordinary differential equations, quadrature of oscillating functions, computation of derivatives and QuasiMonteCarlo integration. We sincerely thank the authors of the papers and the anonymous referees helping us to carefully review the papers included in this first issue of the first volume of JAS.